Chinese consumers’ psychology and behavior of the foods with nutrition claims based on AISAS model - Huang, Zeying; Li, Haijun; Huang, Jiazhang (Frontiers in Nutrition, 2024)
We analyzed the impact of nutrition claims on Chinese consumer psychology and behavior process based on the theoretical framework of AISAS (Attention-Interest-Search-Action-Share) model. Design: To adopt questionnaires to collect gender, age, income and other basic information of adult residents and a 5-point Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree) to collect data on residents' attention to nutrition claims, interest in nutrition claims, search on nutrition claim information, purchasing behavior on food with nutrition claims, sharing information on food with nutrition claims. Then to study the relationship between the basic situation of residents and their attention, interest, search, food purchase behavior and sharing of nutrition claims by using exploratory factor analysis, reliability and validity test, structural equation modeling estimation and hypothesis testing. Participants: Chinese adults Setting: Multi-stage stratified random sampling method was used to collect the valid online questionnaire of 630 Chinese adults from Central, North, East, South, Northwest, Southwest, and Northeast China. Results: Younger adults and those with higher household incomes exhibited heightened attention to nutrition claims. Furthermore, consumers' attention to nutrition claims could be transformed into food information sharing through interest, information search, and food purchase. Consumers' interest in food with nutrition claims could be transformed directly into food purchase. Consumers' search for related information could be directly transformed into food information sharing. Conclusion: Chinese consumers' age and household income could be included in the AISAS model for the foods with nutrition claims, and the consumers' action and share could transform from their interest and search.